2000
DOI: 10.1034/j.1399-3003.2000.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells correlate with angiogenesis and poor outcome in stage I lung adenocarcinoma

Abstract: Angiogenesis is in part related to mast cells. However, the biological significance of mast cells within lung carcinoma remains unclear. Immunohistochemistry was used to stain for tryptase, CD34 and vascular endothelial growth factor (VEGF) in 85 cases of stage I nonsmall cell lung carcinoma. VEGF was found in 33 of 53 adenocarcinomas and 14 of 32 squamous cell carcinomas. Cases of adenocarcinoma had significantly higher mast cell counts than those of squamous cell carcinoma. In adenocarcinoma, mast cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
146
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 25 publications
3
146
3
Order By: Relevance
“…Regarding the impact of mast cells on lung cancer patient outcomes, both adverse and favorable, several contradictory reports have been published. 24,25 This is perhaps due to the mixture of resting and activated mast cells in the previous studies. Interestingly, when resting and activated mast cells were combined together, they were significantly correlated with prolonged survival of NSCLC patients (Figure S3).…”
Section: Discussionmentioning
confidence: 88%
“…Regarding the impact of mast cells on lung cancer patient outcomes, both adverse and favorable, several contradictory reports have been published. 24,25 This is perhaps due to the mixture of resting and activated mast cells in the previous studies. Interestingly, when resting and activated mast cells were combined together, they were significantly correlated with prolonged survival of NSCLC patients (Figure S3).…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that intratumoral macrophages express TP in human malignancies 14,15,[17][18][19] and that activated mast cells express TP in atherosclerotic plaques. 25 Activated mast cells also express VEGF 27 and bFGF. 34 Distinct patterns of TP expression have been observed in human malignancies of various organs.…”
Section: Discussionmentioning
confidence: 99%
“…The association of tumor cell-VEGF expression with increased MVCs and poor clinical outcome in patients with NSCLC has been reported, supporting the clinical significance of VEGF as an important angiogenic factor and prognostic factor in NSCLC. 3,4,27,30 There has been no report on the broad expression of VEGF in tumor-associated stromal cells of NSCLC, although broad expression of TP and bFGF has been found in tumor-associated stromal cells of NSCLC. 24,31 The clinical significance of TP and bFGF as angiogenic factors and/or prognostic factors for NSCLC is still debated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An infiltration of mast cells has been found in a variety of human cancers, including non-small-cell lung cancer (Shijubo et al, 2003), breast cancer (Kankkunen et al, 1997), colorectal cancer (Lachter et al, 1995), basal cell carcinoma (Yamamoto et al, 1997) and pulmonary adenocarcinoma (Imada et al, 2000). The accumulation of mast cells has been associated with enhanced growth and invasion of several human cancers (Ribatti et al, 2001).…”
Section: Mast Cellsmentioning
confidence: 99%